Next-generation cophylogeny: unravelling eco-evolutionary processes. (October 2021) - Blasco-Costa, Isabel; Hayward, Alexander; Poulin, Robert; Balbuena, Juan A.
Abstract : A fundamental question in evolutionary biology is how microevolutionary processes translate into species diversification. Cophylogeny provides an appropriate framework to address this for symbiotic associations, but historically has been primarily limited to unveiling patterns. We argue that it is essential to integrate advances from ecology and evolutionary biology into cophylogeny, to gain greater mechanistic insights and transform cophylogeny into a platform to advance understanding of interspecific interactions and diversification more widely. We discuss key directions, such as incorporating trait reconstruction and considering multiple scales of network organization, and highlight recent developments for implementation. A new quantitative framework is proposed to allow integration of relevant information, such as quantitative traits and assessment of the contribution of individual mechanisms to cophylogenetic patterns. Highlights: Cophylogeny provides an appropriate setting to untie how the ecological and evolutionary facets of species interactions operate. The study of phylogenetic agreement between the evolutionary histories of two groups of symbionts started as a means to analyze constraints and predictability in their interactions and codiversification. More recently, it has attracted the attention of other areas in a quest to understand phylogenetic signal in community assembly and geographical distributions of species. Whilst the field has fostered the development of a battery of tools to elucidate cophylogenetic patterns in symbiotic associations, linking patterns to mechanisms remains the major outstanding challenge. Incorporating current trends in eco-evolutionary research could propel forward cophylogenetic principles and analyses.